Health economics in Africa from 1991 to 2020: A systematic review - Xiao Meng; Gang Mu; Jiaxuan Tong (AOSIS, 2022)
This systematic review was conducted to identify, evaluate and characterize the overall progress of health economics research conducted for Africa. Health economics studies carried out from 1991 to 2020 for Africa were retrieved from the EconLit database using relevant searching strategies. According to the methodology of Preferred Reporting Items for Systematic Review and Meta-Analysis, qualified journal papers were included. Using bibliometrics, we ran a series of analyses on authorship, studied countries, affiliations, and countries of origin, journals, and research topics. A total of 2935 studies were screened, and 178 were included in this review. We observed that the determinants of illness is the most researched topics. The United States, World Bank, University of California Berkeley, are respectively the most influential countries, world organizations, and academic institutions in the field of health economics of Africa. HIV/AIDs is still the leading health issue in highly cited health economics studies in Africa. Health Policy and Planning is the most productive and academically influential journal, and Kenya is the most studied country by health economists among all African countries. African health systems are vulnerable compared to developed countries, as many of them are underfunded. The academic strength in Africa is much weaker than that of leading health economics countries. Even within the continent, the academic development and the attention it receives are uneven. More influential health economics studies of Africa should be published in addition to the disease focus of HIV/AIDS.